Soil Moisture Contents as a Determining Factor Machinery Selection - D. E1fadil, Abdelkarim; A. Ali, Mohammed; I. Mohammed, Hassan (المجلة الزراعية; مجلد 2 عدد 2 (2004), 2021)
A simulation model to predict the daily fluctuations of soil moisture  content was developed using the Versatile Soil Moisture  Budget (VSMB) equation by employing pascal computer language.  The model was tested against actual  field data and showed fairly accurate results.  The correlation coefficient 0.99 .